Evaluation of obstetric management of women with macrosomic foetuses in two Level 3 maternity hospitals in France and identification of predictive factors for obstetric and neonatal complications. (July 2022) - Larad, R.; Ishaque, U.; Korb, D.; Drame, S.; Coutureau, C.; Graesslin, O.; Sibony, O.; Gabriel, R.
Abstract: Objective: Foetal macrosomia is associated with high maternal and neonatal morbidity; however, obstetric management of suspected macrosomia has not been well defined. This study aimed to analyse obstetric management in a population of women who delivered macrosomic new-borns and assess maternal and neonatal outcomes and risk factors for complications in such cases. Study design: This two-centre retrospective study conducted in France over a 10-year period comprised 1724 women who had delivered macrosomic new-borns (defined as those whose weight was > 90th percentile according to the Association of Users of Computerised Records in Perinatology, Obstetrics, and Gynaecology curve) from 37SA. Results: In this study, the caesarean section and instrumental extraction rates were 24.1% and 15.7%, respectively, and the postpartum haemorrhage rate was 7%. The rate of shoulder dystocia was 23.1% (including brachial plexus injuries, 0.4%; and clavicular fractures, 2.0%). Significant risk factors for caesarean section were maternal height < 160 cm, nulliparity, history of caesarean section, excessive uterine height, induction of labour and duration of labour > 10 h. The risk factors for shoulder dystocia were maternal height < 160 cm and instrumental extraction. Conclusion: The study findings may help determine predictive factors for an unfavourable outcome at the time of delivery of a macrosomic foetus, thus allowing clinical teams to better anticipate and manage potential complications.